2011
DOI: 10.1186/1472-6955-10-23
|View full text |Cite
|
Sign up to set email alerts
|

Preconditions for successful guideline implementation: perceptions of oncology nurses

Abstract: BackgroundAlthough evidence-based guidelines are important for improving the quality of patient care, implementation in practice is below expectations. With the recent focus on team care, guidelines are intended to promote the integration of care across multiple disciplines. We conducted an exploratory study to understand oncology nurses' perceptions of guideline implementation and to learn their views on how their experiences affected the implementation.MethodsA qualitative study was used with focus group int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 31 publications
(48 reference statements)
3
26
0
Order By: Relevance
“…Meanwhile, constructivist grounded theory also emphasising on revealing patterns and connections rather than to linear reasoning and emphasises understanding rather than explanation (Charmaz, ). In this study, we found the factors ranging from the evidence level, nurses level, patient level, system level and outside system level, which were generally consistent with the literature from other countries (Ploeg, Davies, Edwards, Gifford, & Miller, ; Solomons & Spross, ; Yagasaki & Komatsu, ), as well as the previous published Chinese surveys (Chien et al., ; Wang et al., ; Zhou et al., ). However, this study also extended the results of previous studies by further exploring the blurred boundaries between facilitators and barriers, influences from Chinese cultural impact and project leaders' roles, as well as an emphasis on the importance of point of care in evidence‐based nursing.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, constructivist grounded theory also emphasising on revealing patterns and connections rather than to linear reasoning and emphasises understanding rather than explanation (Charmaz, ). In this study, we found the factors ranging from the evidence level, nurses level, patient level, system level and outside system level, which were generally consistent with the literature from other countries (Ploeg, Davies, Edwards, Gifford, & Miller, ; Solomons & Spross, ; Yagasaki & Komatsu, ), as well as the previous published Chinese surveys (Chien et al., ; Wang et al., ; Zhou et al., ). However, this study also extended the results of previous studies by further exploring the blurred boundaries between facilitators and barriers, influences from Chinese cultural impact and project leaders' roles, as well as an emphasis on the importance of point of care in evidence‐based nursing.…”
Section: Discussionsupporting
confidence: 91%
“…It must be emphasized that this is a worked example of a theory in practice, not a formal data analysis or review, but it does draw on information from seven studies [81-87] that have met the quality criteria for inclusion in a systematic review of qualitative studies of nursing guideline implementation informed by Normalization Process Theory.…”
Section: Introductionmentioning
confidence: 99%
“…Use of immediate feedback techniques has been observed to be more effective than traditional tactics, such as didactic education or passive dissemination of information . Likewise, facilitating nurses' understanding of the rationale, or the “why,” behind such guideline recommendations can help nurses align their practice with evidence‐based guidelines …”
Section: Discussionmentioning
confidence: 99%